MEMBANGUN KERANGKA FILOSOFIS PENDIDIKAN YANG BERBASIS PADA PROBLEM SOSIAL - Sembodo Ardi Widodo (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
This article is intended to provide philosophical insight of the importance of the educational concept based on social problems. Social problems like poverty, unemployment, moral deterioration, corruption, social violence, and others arise because there is malfunction of education or education institutions in Indonesia in solving those problems. Recently the developing character education must be accompanied by the spirit of progressivism and reconstructive education philosophy. In the west, both of the philosophical ideologies are designed to create progress and social integrity. Education curriculum is consciously directed to deal with the gap and the social life problem, both in relations between the community and the natural environment and the relationship between societies in politics, economic, and socio-cultural. If the concept of education in Indonesia is not built and directed to deal with social life in which taking part in solving the recent social problem widely, the education will only produce graduates who do not care for various social problems faced by the community and the country. Furthermore, the development of science, technology, and information in the globalization era not only give the advantage and efficiency but also have a negative impact on people’s behavior individually or in groups, and all of them must be anticipated and coped by education.